Peran Pelatihan Dengan Metode On The job Training dan Metode Apprenticeship Untuk meningkatkan Kinerja Karyawan Pada perusahaan Labbaik Chicken Kota Serang - Ahyakudin Ahyakudin; M. Ainun Najib; Dede Haryadi (FEB Universitas Sultan Ageng Tirtayasa, 2019)
Training is a way to build human resources towards an era of globalization that is full of competition and challenges. Therefore, training activities cannot be ignored, especially in facing an era of increasingly fierce competition, it can be assumed that training and human resource development are very important for employees to work better and better at the work being held or will be held. This is an effort to prepare the workforce or employees to face job duties that are considered not mastered in their field, including companies that we take as objects of research on the training and development of employees are employees of the Chiken Labbaik company Serang City which is located at Jl. Raya Cipocok T-junction Miyabon in front Alfamidi Cipocok - Serang - Banten prospective permanent employees (apprentices) are trained directly by the supervisior who reports directly to the Branch Manager. Descriptive method is a method of examining the status of a group of people, an object, a set of conditions, a system of thought, or a class of events in the present. Conclusion Training with the on the job training method and the Apprenticeship Method are more focused on increasing the ability and expertise of Labbaik Chicken company employees relating to the position or function that is the responsibility of the individual concerned at present (current job oriented). The goal to be achieved from a training program is to improve individual performance in the Chicken Labbaik company.